Empowering Education: Unveiling The Transformative Potential of Pedagogical Competence for Educator and Learners - Bagea, Ishak; Bagea, Arfin; Bakar, Abu (JURNAL INOVASI DAN MANAJEMEN PENDIDIKAN, 2023)
Paper writing aims to explain the empowering education unveiling the transformative potential of pedagogical competence for educator and learners. Pedagogics is a science that discusses education, namely the science of children's education. So pedagogic explains the ins and outs of children's education, pedagogic is a theory of children's education. Pedagogics as a science is needed by teachers. The task of the teacher is not only to teach to convey or transform knowledge to students at school, but the teacher has the task of developing the personality of his students in an integrated manner. The teacher develops the child's mental attitude, develops the child's conscience or the child's heart so that the child will be sensitive to humanitarian issues, human dignity, as well as the teacher only develops children's skills, life skills in society so that he is able to face all the problems of his life. Conclusion in writing papers: pedagogy competence is a set of knowledge, skills, and behaviors that must be possessed, lived and mastered by teachers or lecturers in carrying out professional duties. This type of research uses qualitative research by means of researchers conducting observations, interviews and documentation with key informants and supporting informants, namely, teachers and students at the Muhammadiyah Kendari Private High School, and the novelty of the results of this research will be useful for the development of science, especially related educational sciences. how teachers and lecturers must master pedagogical competence, social competence, personality competence and social competence.  Conclusion: pedagogical competence has a central role in shaping quality and relevant education. The transformative potential of pedagogical competence not only enriches students' learning experiences, but is also the key to the sustainability and success of the education system in the future. Therefore, continuous efforts in developing and strengthening pedagogical competence need to be implemented as a long-term investment to improve the quality of education.